Premature Arterial Disease Associated with Familial Antithrombin III Deficiency - Johnson, E J; Prentice, C R M; Parapia, L A (Thrombosis and Haemostasis, 1990)
Antithrombin III (ATIII) deficiency is one of the few known abnormalities of the coagulation system known to predispose to venous thromboembolism but its relation to arterial disease is not established. We describe two related patients with this disorder, both of whom suffered arterial thrombotic events, at an early age. Both patients had other potential risk factors, though these would normally be considered unlikely to lead to such catastrophic events at such an age. Thrombosis due to ATIII deficiency is potentially preventable, and this diagnosis should be sought more frequently in patients with arterial thromboembolism, particularly if occurring at a young age. In addition, in patients with known ATIII deficiency, other risk factors for arterial disease should be eliminated, if possible. In particular, these patients should be counselled against smoking.
Keywords: Antithrombin III; Arterial thrombosis; Stroke